Pengaruh Dukungan Sosial Orangtua dan Teman terhadap Career Search Efficacy Mahasiswa di Jawa Barat - Indah Puspitasari; Gianti Gunawan; Meta Dwijayanthy (Humanitas (Jurnal Psikologi), 2022)
Choosing a career is important for things for collage students because a career is not only for life but also becomes a way to actualizing their potential. To actualize their abilities optimally, the process of career exploration and choosing the right career is important. Collage students who are in the final stages of their education process need to have career search efficacy so that they have confidence to be able to explore careers so that they can finally choose jobs that match with their self-concept. One of the successes of career search efficacy is influenced by social support. The main social support is obtained from parents and peers. This study aims to determine the role of social support from parents and peers on collage students career search efficacy  in West Java. The number of participants was 210 people with an age range of 18-25 years. The results showed that social support from parents and peers, had an influence on collage students career search efficacy  in West Java (p <0.05, R2 = 0.113).